Effect in vitro of furapyrimidone on adult worms and microfilariae of Brugia malayi - Xi Yu-rui; Nie Jin-hua; Xu Yu-xin (Acta Pharmacologica Sinica, 2016)
Furapyrimidone, 1-[(5-nitrofurayl-2) methyene amino]-tetrahydropyrimidine-2-one, is a new antifilarial agent discovered in China. Its effects on adult worms and microfilariae of periodic Brugia malayi were studied in calf serum-Tyrode solution (1:20) containing 0.5% glucose. Furapyrimidone was lethal to adult worms and microfilariae and suppressed ♀ worms to release microfilariae at 1 μg/ml. When adult worms were kept in a medium containing furapyrimidone 50 μg/ml, the worms gradually lost their motility and died after 20 h. When adult worms were placed in furapyrimidone 1 μg/ml, the release of microfilariae by ♀ worms was suppressed and the survival time of adult worms was much shorter than that of controls (P